Book review: Calkin, S. 2018. Human Capital in Gender and Development. (October 2019) - Marzi, Sonja
Calkin, S. 2018. Human Capital in Gender and Development . Abingdon, Oxon: Routledge. 190 pp. £115 (hardback). ISBN: 9781138697348.